PENGGUNAAN PREPOSISI DAN KONJUNGSI DALAM TEKS DESKRIPSI SISWA KELAS VII SMP NEGERI 11 PADANG - Lina Handayani; Eva Fitrianti; Susanti Marisya (Ekasakti Educational Scientific Journal, 2025)
Background research shows that the language skills that students must have in order to communicate effectively are to master four skills, namely listening skills, speaking skills, reading skills and writing skills. The objectives of this research are as follows. First, describe the form and function of prepositions in the descriptive text of class VII students at SMP Negeri 11 Padang. Second, to describe the form and function of conjunctions in the descriptive text of class VII students at SMP Negeri 11 Padang. This type of research is qualitative research using descriptive methods. The data used in this research are words in the form of prepositions and conjunctions in the descriptive text of class VII students at SMP Negeri 11 Padang. The data source in this research is descriptive text written by class VII students of SMP Negeri 11 Padang. The instrument of this research is your own research. Assisted with student work sheets, data collection formats and documents. Based on the results of the research and discussion, two things were concluded. First, the form and function of prepositions used in the description text of class VII students of SMP Negeri 11 Padang were found to be 72. These prepositions included 9 prepositions on, 11 prepositions from, 2 prepositions since, 1 preposition with, 32 prepositions in, 4 prepositions for , 1 preposition would, 4 prepositions like, and 1 preposition by. The most frequently found preposition is the preposition at and the least frequently found prepositions are the prepositions with, will, and by. Second, there were 165 forms and functions of conjunctions used in the description text of class VII students at SMP Negeri 11 Padang. The conjunctions included 70 conjunctions and, 9 conjunctions or, 2 conjunctions but, 3 conjunctions so, 1 conjunction until, 1 conjunction although , 3 conjunctions although, 11 conjunctions because, 15 conjunctions with, 52 conjunctions which.